Dead man down [videorecording (DVD)] - Oplev, Niels Arden, 1961-; Farrell, Colin, 1976-; Rapace, Noomi, 1979-; Cooper, Dominic, 1978- (Sony Pictures Home Entertainment, 2013)
In New York City, a crime lord's right-hand man is seduced by one of his boss's victims, a woman seeking retribution.